PENGARUH DESTINATION IMAGE KABUPATEN SUMENEP DAN KEPUASAN WISATAWAN TERHADAP LOYALITAS WISATAWAN SURABAYA - Dewi Nuzila Ramadanita; Juliani Dyah Trisnawati; Antonius Budhiman Setyawan (Perpustakaan Universitas Surabaya, 2020)
The purpose of this paper is to explore both the cognitive and affective images and examine the effects of destination image through both aspects on satisfaction levels and tourist loyalty. The data used in this study comes from primary data, namely data obtained through the distribution of questionnaires. This measurement uses the interval measurement level, which is a measurement that has the same distance and clear difference. This study uses a quantitative approach through statistical testing. Tests conducted using Structural Equation Modeling (SEM) with the help of Analysis of Moment Structured (AMOS 16). The results showed that the cognitive image have positive significant effect to affective image. Cognitive image has a significant positive effect on tourist satisfaction. Affective image has a positive effect on tourist satisfaction. While cognitive image, affective image, and tourist satisfaction does not affect the tourist loyalty.